High‐Gain and Low‐Driving‐Voltage Photodetectors Based on Organolead Triiodide Perovskites. (21st January 2015) - Dong, Rui; Fang, Yanjun; Chae, Jungseok; Dai, Jun; Xiao, Zhengguo; Dong, Qingfeng; Yuan, Yongbo; Centrone, Andrea; Zeng, Xiao Cheng; Huang, Jinsong
Abstract : Solution‐processed organometal trihalide perovskite photodetectors show a high photoconductive gain of above 400 across the UV to NIR range at a very low bias of −1 V. The charge traps caused by large concentrations of Pb 2+ cations at the top surface of the perovskite film are critical for achieving high gain in these devices via a trapped‐hole‐induced electron injection mechanism.